2007
DOI: 10.1177/0193841x06297243
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Risk for Obesity by Promoting Self-Regulation and Decision-Making Skills

Abstract: The overall aim of the two school-based pilot studies was to evaluate whether an approach to prevention that focused on changing child impulse control, decision making, and social competence can be effective in changing attitudes toward food intake and physical activity as risk factors for obesity. The strategy used was to translate specific components of one evidence-based program for violence prevention (Promoting Alternative Thinking Strategies: PATHS) into an elementary school curriculum program for obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 39 publications
2
61
0
1
Order By: Relevance
“…In the field of childhood obesity prevention focusing on ER, to our knowledge there is only one pilot study and two ongoing studies (147)(148)(149) . A school-based pilot intervention translated specific components of a violence and substance abuse programme into a lifestyle intervention.…”
Section: Interventions In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of childhood obesity prevention focusing on ER, to our knowledge there is only one pilot study and two ongoing studies (147)(148)(149) . A school-based pilot intervention translated specific components of a violence and substance abuse programme into a lifestyle intervention.…”
Section: Interventions In Childrenmentioning
confidence: 99%
“…Emotion regulation and childhood obesitytoward self-regulation of appetite and positive changes in food and lifestyle (147) . A randomised clinical trial and prospective study conducted in 779 adolescents and their parents applied a cognitive-behavioural skills intervention combined with nutrition education and physical activity.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%
“…144,145 An intervention study that aimed to develop the self-regulatory skills of obese children found that effects of the treatment on the children's weight was relatively short-lived following the end of the intervention, but that development of better self-regulatory skills during the intervention was associated with a slower rate of post treatment weight gain. 144 A study that focused on promotion of self-regulatory skills in severely obese adults found that as these skills increased, so did perceived self-efficacy in relation to controlled eating, which in turn was associated with BMI change.…”
Section: Theoretical Perspectives On Factors Influencing Self-regulatmentioning
confidence: 99%
“…Since, overweight children face significant risk of remaining obese and health risks in adulthood, early intervention and prevention efforts are needed to address this serious health problem [2]. Riggs et al suggested that prevention programs aimed at improving knowledge about healthy eating and exercise, to encourage the development of healthy lifestyles and prevent obesity are needed [3]. Translating effective intervention into community-based prevention programs is an important goal for researchers [4].…”
Section: Introductionmentioning
confidence: 99%